SYSTEMIC LUPUS ERYTHEMATOSUS AND INFECTIVE ENDOCARDITIS: CLINICAL AND DIAGNOSTIC PARALLELS AND IMAGINARY MIMICRY - S. P. Filonenko; A. A. Nikulina; E. A. Smirnova; E. V. Korotchenko (Klinicist)
Aim of the study – draw attention to the differential diagnosis of systemic lupus erythematosus (SLE) and infective endocarditis.Materials and methods. Patient A., 44 years old, was admitted to the cardiologic department of Ryazan Regional Clinical Cardiology Clinic diagnosed with probable infective subacute endocarditis, glomerulonephritis, with complaints of weakness, fatigue, increase in body temperature up to 37.7 °C preferably in the evening, dry cough, shortness of breath on mild exertion, swelling of legs and feet. In early October 2015, the patient's body temperature increased up to 37.8 °C, there was a dry cough. Patient was treated on an outpatient basis for acute respiratory viral infections with antibiotics, decreased body temperature. Acute deterioration of the condition was observed in mid-October: severe shortness of breath even on mild physical exertion, heart rate increased, as well as lower limb edema, blood pressure (BP) increased up to 240/140 mmHg. The patient was hospitalized in the therapeutic department. Against the background of the treatment (antibiotics, antihypertensive agents, diuretics, digoxin) patient’s condition was improved: shortness of breath decreased, as well as the heart rate, limb edema, blood pressure down to 180/110–190/120 mmHg. However, there was persistent proteinuria (0.33–1.65–3.3 g/L), low grade fever persisting in the evening. On admission to the cardiological department of Ryazan Regional Clinical Cardiology Clinic patient underwent the following survey: assessment of lab parameters in dynamics, electrocardiography, heart echocardiography, computed tomography (CT) of lungs.Results. We revealed left ventricular hypertrophy on heart ultrasonography; an increase in the volume of left atrium, right ventricle, right atrium; mitral, aortic, tricuspid valve insufficiency (grade II regurgitation); pulmonary hypertension; on lung CT – the picture of hydrothorax on the right side, hydropericardium. General analysis of the urine revealed proteinuria equal to 3.3 g/L. These data, combined with the history of the disease (fever for several months) confirmed diagnosis of infective endocarditis, despite the absence of vegetations on heart valves. However, high degree of proteinuria required differential diagnosis with systemic connective tissue diseases, such as system lupus erythematosus. Additional examination revealed increased titers of antinuclear factor (1:5120) antibodies (AB) to the double-stranded deoxyribonucleic acid (DNA) (93 IU/mL). In this regard, and due to an increase in proteinuria up to 10 g/L we re-assessed diagnosis: systemic lupus erythematosus, acute course, grade III of activity with the affection of kidneys (lupus nephritis with nephrotic syndrome and impaired renal function, glomerular filtration rate equal to 35 mL/min), serous membranes (hydrothorax on the right side, hydropericardium), heart (moderate insufficiency of mitral, aortic, tricuspid valve (grade II regurgitation), respiratory system (grade I pulmonary hypertension), haematological disorders (anemia, thrombocytopenia), seropositive for antibodies to double-stranded DNA, anti-nuclear factor; secondary hypertension.Conclusion. This case illustrates difficulties of differential diagnosis between system lupus erythematosus and infective endocarditis, especially in the early stages, when there are still no data of additional examinations.